The theory of value and distribution in economics : discussions between Pierangelo Garegnani and Paul Samuelson - Kurz, Heinz-Dieter (Routledge studies in the history of economics ;, 2013)
This new volume explores two alternative economic theories - the classical theory and the marginalist or neoclassical theory- through a discussion between two eminent economists, Pierangelo Garegnani and Paul Samuelson.The key themes of the volume are the difference in approaches to the explanation of the distribution of income and relative prices, and therefore different approaches to all other economic problems, in particular capital accumulation and economic growth. The book discusses whether there is a 'classical' approach to the theory of value and distribution at the cor.